HIF3A cord blood methylation and systolic blood pressure at 4 years - a population-based cohort study - Mansell Toby; Burgner David; Ponsonby Anne-Louise; Collier Fiona; Pezic Angela; Vuillermin Peter; Juonala Markus; Ryan Joanne; Saffery Richard (TAYLOR & FRANCIS INC, 2022)
Methylation levels at the hypoxia-inducible factor 3 alpha gene (HIF3A) in blood have been linked to body mass index (BMI) in adults. Despite evidence implicating HIF3A in angiogenesis and metabolism, no studies have examined links between HIF3A methylation in early life and cardiovascular health. Here, we investigated the relationship between HIF3A methylation in blood at birth and 12 months of age with cardiovascular measures at 4 years. We also examined influences of prenatal exposures, birth outcomes, and genetic variation. Methylation of two HIF3A promoter regions in cord blood was measured using Sequenom EpiTYPER mass-spectrometry. The first promoter region was also measured in 12-month blood. Four-year cardiovascular measures included blood pressure, pulse wave velocity, and aortic and carotid intima-media thickness. Associations were tested using partial correlation tests and linear regression modelling. Methylation of the first HIF3A promoter in cord and 12-month blood was not associated with four-year measures. There was modest evidence of an association between DNA methylation at the second HIF3A promoter in cord blood and four-year systolic blood pressure (n = 353, r = 0.12, p = 0.03). In sex-stratified analysis, methylation of the second promoter was modestly associated with systolic and diastolic blood pressure (r = 0.16, p = 0.03 for both) in males only. In conclusion, HIF3A methylation at birth shows some evidence of an association with later blood pressure in childhood. Further work should determine whether this relationship persists into later childhood, and should assess potential functional links between HIF3A methylation and cardiovascular health more generally.